Molecular analysis of the yellow gene (y) region of Drosophila melanogaster. - Biessmann, H (1985)
The yellow gene (y) is involved in pattern-specific melanin pigmentation of the cuticle of the adult fly and of larval mouth parts of Drosophila melanogaster. I have isolated some 70 kilobases (kb) of contiguous DNA from the y region. Chromosomal aberrations of y1-type alleles (null alleles) and y2-type alleles that give rise to characteristic pattern mosaicism of pigmentation were mapped by Southern blot analysis. The y2 allele is associated with the insertion of a "gypsy" transposable element 0.9 kb distal to the putative y coding region. A 3.1-kb region to which breakpoints of all y1-type alleles could be mapped is homologous to a 2.0-kb polyadenylylated mRNA, the expression of which is specifically regulated in development. This putative y gene transcript is present at high levels in pupae when melanization of the adult cuticle occurs, but its steady-state levels change dramatically during development, being highest in late embryos prior to hatching. This suggests that, in addition to melanin synthesis and/or deposition, the y gene product may have a role in other possibly neural functions.